PENGARUH LIKUIDITAS, PROFITABILITAS, SOLVABILITAS, DAN RASIO PASAR TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017 - 2020 - Lase, Yotam Terkelin; Silalahi, Esli (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to examine the effect of Liquidity, Profitability, Solvency, and Market Ratio on the stock prices of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. The study population was 185 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sampling technique in this study was carried out using a purposive sampling method, namely a sampling technique with several criteria that must be met. The samples used in this study were 39 companies. This study uses secondary data with documentation techniques which can be accessed through www.idx.co.id. The data analysis technique used is multiple linear regression analysis by conducting t and F tests. The results of hypothesis testing show that Liquidity (Current Ratio) and Market Ratio (Price to Book Value) have a positive and significant effect on the stock prices of manufacturing companies listed on the Stock Exchange Indonesia for the 2017-2020 period, Profitability (Return On Assets) and Solvability (Debt to Equity Ratio) have a negative and significant effect on the stock prices of manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Simultaneous testing that Liquidity (Current Ratio), Profitability (Return On Assets), Solvency (Debt to Equity Ratio), and Market Ratio (Price to Book Value) have a simultaneous and significant effect on the stock prices of manufacturing companies listed on the Indonesia Stock Exchange period 2017-2020. The coefficient of determination of 61.6% means that variations in Current Ratio, Return On Assets, Debt to Equity Ratio, Price to Book Value are able to explain variations in stock prices of 61.6% while the remaining 38.4% is explained by other variables not included in the model.